Ect And Psychotherapy Combination In Treatment Of Affective Disorders In Structure Of Addictions. Analisis Of Efficaсy - GrigorianА. Z. (Psychiatry, Neurology and Medical Psychology, 2016)
In order to analyze the effectiveness of the method of electroconvulsive therapy in patients with affective disorders in the structure of addictions, using clinically psychopathological method, in which the verification and quantification of psychopathology was performed using the rating Positive and Negative Syndrome Scale (PANSS), were examined 30 patients with polydrug use. On the basis of an evaluation scale of positive and negative symptoms (PANSS), derived from the study concluded that the high efficiency of the method of electroconvulsive therapy for mood disorders in the structure of addictions.